Impact of different ultraviolet radiation on the ability to accumulate vitamin D2 and the composition of different mushroom strains: Vitamin accummulation potential of different mushrooms - Kamal, Shwet; Saikia, Siddhartha Proteem; Barh, Anupam; Annepu, Sudheer K; Srivastava, Anuradha; Sharma, Ved Parkash; Kashyap, Radhika; Begum, Marium; Kumar, Anil (Mushroom Research, 2025)
Vitamin D deficiency is one of the most common nutritional and medical condition affecting more than 50 per cent of the world’s population. There are very few foods having vitamin D such as fatty fish, liver, eggs and some fortified foods. Mushrooms exposed to UV radiation are an excellent source of dietary vitamin D2. The study was conducted to see the Vitamin D accumulation potential of different strains of button, oyster, milky, shiitake, paddy straw and lion’s mane mushrooms upon UV light treatment for their potential use as vitamin D supplement. Four different UV treatments have been evaluated along with effect of sun light in this study. Post-harvest UV-B (209-310 nm) treatment for a period of two hours has resulted in significant increase of Vitamin D2 content (up to 300%) in all the tested strains of mushrooms with a maximum in Lentinula edodes (shiitake) and Hericium erinaceous (Lion’s Mane) mushroom.